Thyroid Storm and Complete Heart Block after Treatment with Radioactive Iodine. (11th June 2018) - Vennard, Kaitlyn; Gilbert, Matthew P.
Abstract : Thyroid storm is a rare endocrine emergency characterized by dysfunction of multiple organ systems. Thyroid storm is more common in Graves' disease and can be precipitated by surgery, trauma, infection, metabolic abnormalities, iodine load, and parturition. We present a diagnostically challenging case of thyroid storm precipitated by radioiodine therapy and accompanied by bradycardia, a rare but life-threatening complication related to treatment for hyperthyroidism.